Achieving blood pressure targets and antihypertensive effects through metabolic surgery in type 2 diabetes patients with hypertension. Issue 4 (30th November 2020) - Sun, Fang; Zhou, Xunmei; Li, Qiang; Li, Yingsha; Zhang, Hexuan; Yan, Zhencheng; He, Hongbo; Zhao, Zhigang; Ke, Zhigang; Gao, Yu; Li, Fan; Tong, Weidong; et al.
Short Summary: This was a prospective study of 535 diabetes patients who underwent metabolic surgery ( n = 112) and medical treatment ( n = 423). Metabolic surgery decreased both office systolic blood pressure (SBP) and diastolic blood pressure (DBP) and also significantly reduced ambulatory SBP (132 ± 2 vs. 119 ± 1 mmHg, p < 0.0001). Moreover, the rate of achieving the target SBP of 130 and 140 mmHg was also significantly higher in the surgery group. The defined daily dose of antihypertensive medication was significantly decreased in after surgery. Furthermore, metabolic surgery markedly improved the risks of atherosclerotic cardiovascular disease. In conclusion, metabolic surgery can effectively achieve the BP target and improve multiple metabolic dysfunction in type 2 diabetes mellitus patients with hypertension. Abstract: Aims: The effect of metabolic surgery compared with that of conventional therapy on target blood pressure (BP)and defined daily dose (DDD) of antihypertensive drugs in type 2 diabetes (T2DM) patients with hypertension remains unclear. This study aimed to investigate the differences in target BP and DDD between metabolic surgery and conventional treatment in T2DM patients with hypertension. Materials and methods: This was a prospective study of 535 diabetes patients who underwent metabolic surgery ( n = 112) and medical treatment ( n = 423). Changes in the target BP from baseline to every follow‐up were analysed. Results: Metabolic surgery decreased both office systolic and diastolic BP (DBP) and also significantly reduced ambulatory systolic BP (SBP; 132 ± 2 vs. 119 ± 1 mmHg, p < 0.0001), but not DBP (78 ± 1 vs. 76 ± 1 mmHg, p = 0.177). Patients maintained their SBP at <120 mmHg after 2 years (50% vs. 1.9%, p < 0.0001). Moreover, the rate of achieving the target SBP of 130 and 140 mmHg was also significantly higher in the surgery group, and this started from the initial 6 months after commencing treatment to the end of follow‐up. The dosage (DDD: 1.44 ± 0.65 vs. 0.32 ± 0.05, p < 0.001) of antihypertensive medication was significantly decreased after metabolic surgery. Furthermore, metabolic surgery, but not medical treatment, markedly improved the risks of atherosclerotic cardiovascular disease. Conclusions: Metabolic surgery can effectively achieve the BP target and reduce the usage of antihypertensive medications as well as improve multiple metabolic dysfunction in T2DM patients with hypertension. This study provides an alternative approach to antagonize the metabolic related hypertension.